Experimental grubicide application methods to control cattle grubs - Knapp, F.W.; McKee, M. (Kansas Agricultural Experiment Station, 2011)
During the past year a new grubicide application method has been tested for use in controlling cattle grubs. Called the pour-on method, it consists of pouring a small amount of a special formulation of systematic grubicide along the back line of an animal before grubs appear in the back.
Keywords: Beef; Grubicide